Postmagmatic Tectonic Evolution of the Outer Izu‐Bonin Forearc Revealed by Sediment Basin Structure and Vein Microstructure Analysis: Implications for a 15 Ma Hiatus Between Pacific Plate Subduction Initiation and Forearc Extension. (6th December 2019) - Kurz, W.; Micheuz, P.; Christeson, G. L.; Reagan, M.; Shervais, J. W.; Kutterolf, S.; Robertson, A.; Krenn, K.; Michibayashi, K.; Quandt, D.
Abstract: International Ocean Discovery Program Expedition 352 recovered sedimentary‐volcaniclastic successions and extensional structures (faults and extensional veins) that allow the reconstruction of the Izu‐Bonin forearc tectonic evolution using a combination of shipboard core data, seismic reflection images, and calcite vein microstructure analysis. The oldest recorded biostratigraphic ages within fault‐bounded sedimentary basins (Late Eocene to Early Oligocene) imply a ~15 Ma hiatus between the formation of the igneous basement (52 to 50 Ma) and the onset of sedimentation. At the upslope sites (U1439 and U1442) extension led to the formation of asymmetric basins reflecting regional stretch of ~16–19% at strain rates of ~1.58 × 10 −16 to 4.62 × 10 −16 s −1 . Downslope Site U1440 (closer to the trench) is characterized by a symmetric graben bounded by conjugate normal faults reflecting regional stretch of ~55% at strain rates of 4.40 × 10 −16 to 1.43 × 10 −15 s −1 . Mean differential stresses are in the range of ~70–90 MPa. We infer that upper plate extension was triggered by incipient Pacific Plate rollback ~15 Ma after subduction initiation. Extension was accommodated by normal faulting with syntectonic sedimentation during Late Eocene to Early Oligocene times. Backarc extension was assisted by magmatism with related Shikoku and Parece‐Vela Basin spreading at ~25 Ma, so that parts of the arc and rear arc, and the West Philippine backarc Basin were dismembered from the forearc. This was followed by slow‐rift to postrift sedimentation during the transition from forearc to arc rifting to spreading within the Shikoku‐Parece‐Vela Basin system. Plain Language Summary: This study examines the stress and deformation conditions and timing of extension in the Izu‐Bonin forearc subsequent to subduction initiation by combining seismic images and microstructure analyses on veins and fault zones. By that we also examine a hiatus of 15 Ma between the formation of igneous forearc crust and the formation of sediment basins by forearc extension. This is implemented into an overall tectonic model at lithospheric scale. Key Points: IODP Expedition 352 obtained a 15 Ma hiatus between igneous basement formation and onset of sedimentation along the Izu ‐ Bonin forearc Incipient Pacific Plate rollback is inferred to have triggered forearc extension and syntectonic sedimentation Downslope increase of stretch is inferred to be related to upper plate flexure toward the retreating trench